The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1002/jso.26372
|View full text |Cite
|
Sign up to set email alerts
|

Genetic testing and surgical treatment after breast cancer diagnosis: Results from a national online cohort

Abstract: Background: Genetic testing for hereditary breast cancer has implications for breast cancer decision-making. We examined genetic testing rates, factors associated with testing, and the relationship between genetic testing and contralateral prophylactic mastectomy (CPM).Methods: Patients with breast cancer (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) from The Health of Women Study were identified and categorized as low, moderate, or high-likelihood of the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In particular, despite there being no evidence to suggest that Black women with breast cancer have lower rates of BRCA1/2 pathogenic variants than White women, 3 studies from several states have found that Black women with breast cancer have lower rates of indicated testing than White women. [4][5][6] These inequities are particularly concerning given that Black women are more likely to be diagnosed with breast cancer before age 40 than White women and have higher breast cancer mortality rates. 7,8 The contribution of insurance coverage and access to racial/ethnic disparities in BRCA testing is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, despite there being no evidence to suggest that Black women with breast cancer have lower rates of BRCA1/2 pathogenic variants than White women, 3 studies from several states have found that Black women with breast cancer have lower rates of indicated testing than White women. [4][5][6] These inequities are particularly concerning given that Black women are more likely to be diagnosed with breast cancer before age 40 than White women and have higher breast cancer mortality rates. 7,8 The contribution of insurance coverage and access to racial/ethnic disparities in BRCA testing is not well understood.…”
Section: Introductionmentioning
confidence: 99%